Studi Penelitian Faktor Air Cementitious pada Beton Geopolimer Berbasis Fly Ash (Batu Bara) Berdasarkan Kuat Tekan - Naitkaki, Fridolin A. M. A. Sani; Priskasari, Ester; Roostrianawaty, Nenny (Magister Teknik Sipil, Fakultas Teknik, Universitas 17 Agustus 1945 Surabaya, 2025)
Fly ash based geopolymer concrete is an environmentally friendly alternative that can replace conventional Portland cement based concrete. This study aims to analyze the effect of the water cementitious (W/C) ratio on the compressive strength of Type C fly ash based geopolymer concrete from the Paiton Power Plant, as well as to determine the correlation between the water cementitious ratio and the concrete's compressive strength. The variations of the water cementitious ratio used were 0,35, 0,4, 0,45, 0,5, 0,55, 0,6, and 0,65. The alkaline activator used consisted of 8 M potassium hydroxide (KOH) and sodium silicate (Na₂SiO₃) with a ratio of 3:1. The test specimens, in the form of concrete cylinders (Ø15 cm × 30 cm), were tested at the ages of 3 and 7 days using the room temperature curing method. The results show that the compressive strength of the geopolymer concrete decreases with the increase of the water cementitious (W/C) ratio. At 3 days, the highest compressive strength of 28,42 MPa was achieved at a W/C of 0,35, while the lowest was 17,94 MPa at a W/C of 0,65. At 7 days, the highest compressive strength reached 37,13 MPa (W/C 0,35) and the lowest was 23,89 MPa (W/C 0,65). The concrete slump value increased with the increase in the W/C ratio, with the highest value of 18,4 cm at a W/C of 0,65. The test results conclude that the water cementitious (W/C) ratios of 0,35, 0,4, 0,45, 0,5, 0,55, 0,6, and 0,65 have a significant effect on the compressive strength of geopolymer concrete, where a higher water cementitious (W/C) ratio results in lower compressive strength.